AUnifying Perspective to Understanding Computational Intelligence Techniques and Their Applicability in Various Application - Romyaldy, Romyaldy (MESIN, 2007)
A Unifying Perspective to Understanding Computational Intelligence Techniques andTheir Applicability in Various Applications. Computational intelligence techniques, such as NeuralNetworks, Support Vector Machine (SVM) and Fuzzy Inference System (FIS), has been receiving a largeattention in research area nowadays. Their application has covered vast area from engineering andbusiness. This paper highlight a perspective that could provide newcomer to this field (especially) reasonsand explanations for theirsuch wide range of applications. Throughout thepaper, control applications inwill be used as an example for the implementation of this perspective in real mechanical engineeringapplication.